Celebrity Preachers and The Commodification of Da'wah: A Comparative Study of Traditional Ulama Versus Influencer Hijrah in Indonesia - Lalu Ahmad Zaenuri (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The explosive growth of Islamic preaching content on Indonesian social media since 2015 has produced two strikingly different models of religious authority that share platform space but diverge in nearly every other respect. This article presents a comparative netnographic study of twenty Indonesian da'wah actors H ten traditional ulama grounded in pesantren scholarship and chains of transmission (Typology A) and ten hijrah influencers who built their authority primarily through digital charisma, lifestyle aesthetics, and commercial partnerships (Typology B) observed across YouTube, Instagram, and TikTok over twelve months (July 2024–June 2025). Drawing on 4,200 posts, engagement metrics for 2,400 content units, and semistructured interviews with eight participants, we identify three findings. First, divergent production logics: Typology A produces longform, minimally edited scholarly lectures oriented toward ta'lim (instruction), while Typology B produces shortform, dramatically edited entertainmentoriented content calibrated for algorithmic amplification. Second, a commodification continuum: Typology A maintains relative resistance to commercial partnerships, while Typology B intensively monetizes religious content through brand endorsements, merchandise, and paid events, framing commodification as a form of halal economic sustainability. Third, asymmetric algorithmic legitimacy: platform algorithms consistently reward Typology B with greater reach, yet commentsection dynamics reveal persistent counterlegitimation from audiences who invoke traditional scholarly credentials to challenge influencer authority. We propose the concept of commodified piety to describe a mode of religious performance in which spiritual, economic, and algorithmic value become structurally entangled, and argue that the political economy of platforms not merely individual ambition drives this entanglement.